Pure hydrogen co-production by membrane technology in an IGCC power plant with carbon capture. (11th October 2018) - Giuliano, Aristide; Poletto, Massimo; Barletta, Diego
Abstract: The CO2 capture in Integrated Gasification Combined Cycle (IGCC) plants causes a significant increase of the cost of electricity (COE) and thus determines high CO2 mitigation cost (cost per ton of avoided CO2 emissions). In this work the economic sustainability of the co-production of pure hydrogen in addition to the electricity production was assessed by detailed process simulations and a techno-economic analysis. To produce pure hydrogen a Water Gas Shift reactor and a Selexol ® process was combined with H2 selective palladium membranes. This innovative process section was compared with the more conventional Pressure Swing Adsorption in order to produce amount of pure hydrogen up to 20% of the total hydrogen available in the syngas. Assuming for a base case a hydrogen selling price of 3 €/kg and a palladium membrane cost of 9200 €/m 2, a cost of electricity (COE) of 64 €/MWh and a mitigation cost of 20 €/tonCO2 were obtained for 90% captured CO2 and 10% hydrogen recovery. An increase of the hydrogen recovery up to 20% determines a reduction of the COE and of the mitigation cost to 50 €/MWh and 5 €/tonCO2, respectively. A sensitivity analysis showed that even a 50% increase of cost of the membrane per unit surface could determine a COE increase of only about 10% and a maximum increase of the mitigation cost of further 5 €/tonCO2 . Graphical abstract: Highlights: H2 coproduction makes the CO2 capture economically viable in IGCC plants. WGS, H2 selective Pd membranes and CO2 capture with Selexol ® process are combined. H2 purification by selective Pd membranes and by PSA are compared. Recovery of 20% of total H2 allows 90% CO2 capture at a cost of 5 EUR/tonCO2 . 50% increase of the membrane cost causes about 10% increase of the Cost of Energy.